Ebola: a review on the state of the art on prevention and treatment - Giuseppe La Torre; Vincenzo Nicosia; Maurizio Cardi (Asian Pacific Journal of Tropical Biomedicine, 2014)
The aim of this paper is to highlight the current development in the research field for helping people just exposed to Ebola virus survive (treatment) and to prevent the disease when given at various times after exposure (vaccine). Concerning the treatment, recombinant anti-Ebola monoclonal antibodies and small interfering RNAs that block the expression of essential viral proteins, are the most promising way in stopping the disease when it has already reached the humans. As far as concerns the prevention field, two candidate vaccines have clinical-grade vials available for phase 1 pre-licensure clinical trials, and demonstrated to have a 100% efficacy in studies on non human primates. Well-informed communities can reduce the main ways of spread the infection, by avoiding unprotected home-based care of people who are infected and also by completely modifying traditional burial practices that are way of diffusion of the contagion.